3D surgical planning of pediatric tumors: a review - Pereira, Helena Rico; Barzegar, Mojtaba; Hamadelseed, Osama; Esteve, Arnau Valls; Munuera, Josep (International journal of computer assisted radiology and surgery, 2022)
3D surgical planning for the treatment of tumors in pediatrics using different neuroimaging methods is witnessing an accelerating and dynamic development. Until now, there have been many reports on the use of 3D printing techniques in different aspects of medical practice. Pediatric tumors mainly in the abdomen are among the most medical specialties that benefit from using this technique. The purpose of the current study is to review published literature regarding 3D surgical planning and its applications in the treatment of pediatric tumors and present challenges facing these techniques.
Gesehen am 31.01.2022